Retrospective Evaluation of Palifermin Use in Nonhematopoietic Stem Cell Transplant Pediatric Patients. Issue 4 (May 2017) - Liu, Dazhi; Seyboth, Brian; Mathew, Sherry; Gilheeney, Stephen W.; Chou, Alexander J.; Drill, Esther; Kobos, Rachel
Abstract : Background: Palifermin has been proven to decrease the frequency of severe oral mucositis in adult patients with sarcoma and metastatic colorectal cancer receiving chemotherapy. The impact of palifermin on the incidence of mucositis in nonhematopoietic stem cell transplantation (HSCT) pediatric population receiving chemotherapy has never been reported to date. Patients and Methods: This is a retrospective analysis of pediatric patients who received palifermin as secondary prophylaxis to prevent chemotherapy-induced mucositis at Memorial Sloan Kettering Cancer Center from January 1, 2008 to 2014. Data from electronic medical records on days to mucositis resolution, use of opioids, use of total parenteral nutrition, duration of hospitalization, and antibiotics are collected and presented here. Results: A total of 18 patients received palifermin for secondary prophylaxis after developing mucositis from the prior chemotherapy cycle. Mucositis did not reoccur in the subsequent cycle for 13 of the 18 patients. The majority of patients who received palifermin prophylaxis had decreased opioids and antibiotics use and decreased duration of hospitalization. Six of the 7 patients previously requiring total parenteral nutrition due to mucositis had decreased supplemental nutritional needs following the use of palifermin. Conclusion: Palifermin may provide benefit as secondary prophylaxis in pediatric patients to prevent chemotherapy-induced mucositis.